2021
DOI: 10.1364/ao.411533
|View full text |Cite
|
Sign up to set email alerts
|

The Simons Observatory: modeling optical systematics in the Large Aperture Telescope

Abstract: We present geometrical and physical optics simulation results for the Simons Observatory Large Aperture Telescope. This work was developed as part of the general design process for the telescope, allowing us to evaluate the impact of various design choices on performance metrics and potential systematic effects. The primary goal of the simulations was to evaluate the final design of the reflectors and the cold optics that are now being built. We describe nonsequential ray tracing used to inform the design of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 34 publications
(42 reference statements)
0
13
0
Order By: Relevance
“…A good demonstration of these correlations is shown in Ref [28],. where a more comprehensive review of the SO optics can also be found.…”
mentioning
confidence: 69%
“…A good demonstration of these correlations is shown in Ref [28],. where a more comprehensive review of the SO optics can also be found.…”
mentioning
confidence: 69%
“…The Simons Observatory (SO; Galitzki et al 2018; The Simons Observatory Collaboration 2019) is a next-generation CMB experiment consisting of three 0.42 m small-aperture telescopes (SATs; Ali et al 2020) and one 6 m Large Aperture Telescope (LAT; Parshley et al 2018) in the Atacama Desert of Chile. The LAT utilizes a crossed-Dragone optical design with a pair of 6 m mirrors (Gallardo et al 2018;Gudmundsson et al 2021). The Large Aperture Telescope Receiver (LATR; Orlowski-Scherer et al 2018;Zhu et al 2018; can contain up to 13 optics tubes (OTs) and will cover six frequency bands centered around 27, 39, 93, 145, 225, and 280 GHz with polarization-sensitive dichroic pixels.…”
Section: Introductionmentioning
confidence: 99%
“…The SO LAT is shown in Figure 1 and described in [8]. We compute its beam pattern in the near-field and far-field using physical optics [4,30] implemented in a code we call HoloSim-ML, available at GitHub.com/McMahonCosmologyLab [31].…”
Section: Beam Simulationmentioning
confidence: 99%
“…Simons Observatory (SO) is an ensemble of millimeter-wave telescopes which will observe the cosmic microwave background (CMB) temperature and polarization signals [1,2]. SO comprises one Large Aperture Telescope (LAT) [3][4][5] and three Small Aperture Telescopes (SAT) [6] which together will measure the temperature and polarization anisotropy of the CMB from several degrees to arc-minute angular scales.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation